INQUIRIES LEARNING MODEL TO INCREASE LEARNING OUTCOMES FOR PRIMARY SCHOOL CHILDREN - Stelly V Manawan; Melkian Naharia; Hetty Tumurang (Jurnal Edusci, 2025)
Background. Education is a crucial factor in human life because it can encourage and determine the progress of a nation. Therefore, education is focused on increasing human resources so thateducation can improve human quality in all aspects of life. Education, as one of the most critical sectors in national development, plays a crucial role in improving the quality of life for the Indonesian people. Aims. This study aims to determine how to improve student learning outcomes through the e-inquiry learning model in PAUD children. Methods. This research is a classroom action research (CAR) study, with kindergarten children as the subjects, totaling 30 participants. The data sources are obtained from test results, observations, and questionnaires. Result. Based on the research results, the data obtained from the first cycle of teacher activity is 82%, and the data from student activity is 85%. Meanwhile, teacher activity in cycle II was 92% and student activity was 95%. And children's learning outcomes in the first cycle of 67% and in the second cycle increased by 90%. The child's response to the learning provided by the teacher is also quite good, with kindergarten children expressing pleasure in participating in this learning at a rate of 88%, and those who stated that they were not happy to participate in this learning at a rate of 12%. Conclusion. Thus, it can be concluded that the application of the Inquiry learning model can improve the learning outcomes of kindergarten children in vocabulary development materials. The activities of teachers and kindergarten children have been going well and are receiving a good response from the students.